"All Are Deserving": Racialized Conditions of Immigrant Deservingness in a Catholic Worker Movement-Inspired Non-Governmental Organization. (November 2022) - Jimenez, Anthony M.
Although deservingness considerations are commonly antithetical to the aims of pro-immigrant spaces like Justicia y Paz (JyP), a volunteer-run, Catholic Worker Movement-inspired non-governmental organization in Houston, Texas, they nevertheless materialize. This study explores how and why this happens. Drawing on an inductive analysis of 11 months of ethnographic observation and 36 in-depth interviews with volunteers and migrants at JyP, I argue that in "all are deserving" contexts, pro-immigrant advocates can engage in racialization and perpetuate white supremacy. I find that not all are treated as deserving—that deservingness is conditional on migrants submitting to two racially subordinate positions: (1) workers whose labor benefits the material interests of the white suburban elite and (2) indigent subjects whose impoverishment serves as the basis of spiritual salvation for a predominately white base of volunteers aiming to "serve the poor." This research underscores the limitations of the Catholic Worker Movement-inspired "all are deserving" framework and affords similar pro-immigrant organizations practical insight toward ways to manifest immigrant justice.